As organizações não-governamentais no sistema penitenciário do estado de São Paulo: protagonistas constitutivas de novos modelos prisionais ou reprodutoras dos modelos tradicionais? - Costa, Gizelda Morato (2006)
The present study had for objective to contemplate critically concerning an experience that is happening since the year of 2000 in the system prisoner of the State of São Paulo, through partnership between the State and the call Third Section: the Centers of Resocialization (CRs), constituted to guard condemned individuals. Our investigation and analysis intended to bring until then for the debate academic subjects kept into the walls of the prisons, where members of several segments of the society and the State is trying to create a new model of administration prisoner ". We had, also, the intention of maintaining steadily the debate and the social concern with the thematic of the imprisoned men's human necessity. Necessity these that it comes being neglectful for the State. And, specifically, the State of São Paulo, instead of assuming with responsibility the paper that competes him, it has been allowing the use of the beginning of the subsidied, transferring for organisms of the civil society the responsibilities of attendance social prisoner. And, the problem that is surfacing inside of the prisons CRs it is the form of performance of the ONGs, that is reproducing practices that they are opposed to the beginnings and protected values by the Social Service, for they be not returned to the defense of the social rights, but to the palliative assistance, what doesn't promote the subject holden of rights, with views to the exercise of your citizenship